A fossil aphid gall from the middle Pleistocene sediment in Hyogo Prefecture, western Japan. Issue 3 (27th June 2019) - Tsukagoshi, Minoru; Sawada, Ken; Akimoto, Shin‐ichi
Abstract: We described the external morphology of a fossil insect gall collected from the middle Pleistocene sediment in the Osaka Group of Nishinomiya City, Hyogo Prefecture, western Japan. The fossil was well preserved without major compression and was identified as a gall induced by an aphid species of the genus Nipponaphis (Nipponaphidini: Hormaphidinae: Aphididae), based on its external morphology. This is the first reliable fossil record of an Aphididae gall. This fossil provides evidence that the intimate aphid–plant association can be traced back to the middle Pleistocene, approximately 0.4 million years ago. Abstract : A fossil gall induced by an aphid species of the genus Nipponaphis . This fossil gall was collected from the middle Pleistocene sediments in Hyogo Prefecture, western Japan. This fossil provides evidence that the intimate aphid–plant association can be traced back to the middle Pleistocene, approximately 0.4 million years ago.